A Study on the Response of the Rehabilitation Lower Device using Sliding Mode Controller - Duc, D. M.; Tuy, T. X.; Phuoc, P. D. (Engineering, Technology & Applied Science Research, 2021)
This paper presents the application of the sliding mode controller to simulate the control of a 3 Degree of Freedom (DoF) robot model that supports lower extremity rehabilitation exercises for stroke patients. The 3 DoF robot model has an established dynamic differential equation for each joint. This paper studied the response of links of the research model with a sliding mode controller proposed as the control solution. Matlab software was used in simulations of ankle, knee, and hip joints’ drive for 2 cases, without and with load. Compared with other studies, the research results show that the sliding controller results in slight angular errors when applied to the research model, while the torque of the joints remains low. This result is the basis for calculating and selecting parameters for the actuator when manufacturing the actual equipment.